Languages and Their Registers in Medieval Croatian Culture - Kapetanović, Amir (Studia Ceranea, 2017)
The linguistic situation in medieval Croatia was fairly dynamic. The present article discusses the stratification of linguistic culture in the Middle Ages as regards its division into the three registers (high, middle, low) inherited from ancient rhetoric and poetry and received in the Middle Ages. We conclude that there was no strict division among the three languages according to function in the Middle Ages, and that the languages themselves did not constitute styles or registers. The Old Croatian language possessed all three registers (high, middle, low) already in the Middle Ages. However, the hybrid Čakavian-Church Slavic variety as well as the Croatian redaction of Church Slavic were not used as everyday (in)formal business/colloquial codes, so that they did not develop a middle and low linguistic register.